Systematic investigation on the charge storage behavior of GdCrO3 in aqueous electrolyte. (October 2021) - Nashim, Amtul; Pany, Soumyashree; Parida, K.M.
Highlights: GdCrO3 was prepared by solid state reaction methods. For the first time, the electrochemical properties of GdCrO3 are studied in detail for supercapacitor activity. The specific capacity of GdCrO3 is found to be 227 C/g at the scan rate of 0.5 mV/s in 2M KOH electrolyte with potential range of 0 to 0.6 V. The Nyquist plot, bode plot and the plot of real capacitance vs. imaginary capacitance is well in support of supercapacitive activity of GdCrO3 . GdCrO3 has excellent cyclic retention in 2M KOH at 2A/g after 10, 000 cycles and is found to be 85% which shows its great rate capability. Abstract: The GdCrO3 is prepared by a facile solid state method and the electrochemical properties like Cyclic Voltametery, Galvanostatic charge discharge, impedance, bode plot, etc. is studied in details towards supercapacitor application. The Trasatti method is used to evaluate the capacitive contribution of surface controlled charge component and diffusion control charge component of the electrode material. The specific capacity of GdCrO3 is found to be 227 C/g at the scan rate of 0.5 mV/s in 2M KOH electrolyte with potential range of 0 to 0.6 V. The cyclic retention of the GdCrO3 is found to be 85% after 10, 000 cycles. The battery like behavior of GdCrO3 is found out from its Cyclic voltammetry and Galvanostatic charge discharge curves. GdCrO3 can be considered as a multifunctional material as it combines the property like optical, electrical and magnetic properties. In this paper for the first time the electrochemical properties of GdCrO3 is considered. This work may give worthy information for further investigation on GdCrO3 system.